Impact of World Oil Prices on the Formation of Macroeconomic Policies in Kazakhstan and the European Union: A Comparative Analysis - Baimaganbetova, Meruyert (International Journal of Energy Economics and Policy, 2025)
The study examined the correlation between fluctuations in world oil prices and the development of macroeconomic policies in Kazakhstan and the European Union (EU). Kazakhstan is a country with a resource-based economy that is highly vulnerable to changes in crude oil prices. In turn, the EU has implemented regulatory measures to decouple its economic performance from reliance on fossil fuels. The methods include analyzing the economic structure to determine diversification criteria across sectors and the response of different sectors to price changes; dynamic analysis of the country’s export potential using linear approximation and export structure, enabling the identification of long-term trends; correlation analysis between world oil prices and economic development indicators, export potential, and inflation to identify economic interrelationships and specific aspects of Kazakhstan’s economy. The findings indicate that economic diversification, dominated by the service sector and significant domestic demand, renders the economy more resilient to external shocks. However, the high dependence of export potential on crude oil highlights insufficient diversification of the export base. This underscores Kazakhstan’s strategic role in the global oil market and explains the correlation between world oil prices and the country’s macroeconomic indicators. The data obtained confirm the need for fiscal buffers.